Non Hodgkin's Lymphomas; A New Classification - Machado, Jesus Carlos (2023)
The A. presents some brief considerations about certain pathological aspects of the malignant lymphomas, and makes evidence of the real necessity of continuing specialization on this subject. He informs the creation of the National Committee on Malignant Lymphoma (Instituto Butantan, São Paulo) by the Nacional Cancer Division of the Ministery of Health, that intended to assist in all aspects the Brazilian pathologists on this subject.